Дослiдження адронних множинностей i вiдношень виходiв адронiв у зiткненнях важких iонiв - Oliinychenko, D. R.; Bugaev, K. A.; Sorin, A. S. (Publishing house "Academperiodika", 2018)
We thoroughly discuss some weak points of the thermal model, which is traditionally used to describe the hadron multiplicities measured in the central nucleus-nucleus collisions. In particularly, the role of conservation laws and the values of hard-core radii along with the effects of the Lorentz contraction of hadron eigenvolumes and the hadronic surface tension are systematically studied. It is shown that, for the adequate description of hadron multiplicities, the conservation laws should be modified, whereas the conservation laws are not necessary at all for the description of hadron yield ratios. We analyzed the usual criteria for the chemical freeze-out and found that none of them is robust. A new chemical freeze-out criterion of constant entropy per hadron equals to 7.18 is suggested, and a novel effect of adiabatic chemical hadron production is discussed. Additionally, we found that the data for the center-of-mass energies above 10 GeV lead to the temperature of the nil hadronic surface tension coefficient of about T0 = 147 ± 7 MeV. This is a very intriguing result, since a very close estimate for such a temperature was obtained recently within an entirely different approach. We argue that these two independently obtained results evidence that the (tri)critical temperature of a QCD phase diagram is between 140 and 154 MeV. In addition, we suggest to consider the pion and kaon hardcore radii as new fitting parameters. Such an approach allows us, for the first time, to simultaneously describe the hadron multiplicities and the Strangeness Horn and to get a high-quality fit of the available experimental data.